Perceived Ease of Use and Usefulness of Facebook for Premenstrual Syndrome Health Education - Dwi Sri Handayani; Elsi Dwi Hapsari; Widyandana Widyandana (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2022)
Background: Premenstrual syndrome (PMS) is a collection of physical, psychological and behavioral changes that can be experienced by women of reproductive age. School adolescents who experience PMS symptoms can have an impact on school activities and daily life. One of the efforts to overcome it is through health education about PMS. Health education innovation in adolescents can be done with the use of social media. Social media that can be used as a means of sharing information is Facebook. Objective: This study aims to know the relationship between perceived ease of use and perceived usefulness of Facebook for health education about PMS. Method: Analytic study research design with a cross section approach. The research variable was the perception of ease of use and usefulness of Facebook as a medium of health education about PMS. The population was 320 school teenagers and the samples were taken by purposive sampling as many as 77 school teenagers who experienced PMS symptoms and had received PMS health education on Facebook. The research data were taken using a questionnaire of perceived ease of use (PEOU) and perceived usefulness (PU) and analyzed using a descriptive and contingency coefficient. Results: Facebook was considered easy (63.6%) to be used for health education about PMS and Facebook was considered useful (57.1%) as a medium for health education about PMS. There was a significant relationship between perceived ease of use and usefulness of Facebook as a medium for health education about PMS (pvalue=0,017 ) with a correlation coefficient value of 0.263 indicating that the correlation is weak. Conclusion: Perceived ease of use was related to the perceived usefulness of Facebook. Facebook was easy to use and useful for health education about PMS. Facebook was effective and useful for learning about PMS. Social media can be a medium for health education and help improve the health of school adolescents who experience PMS.